Dabigatran – a case history demonstrating the need for comprehensive approaches to optimize the use of new drugs - Malmstrom, Rickard; Godman, Brian; Diogene, Eduardo; Baumgaertel, Christoph; Bennie, Marion; Bishop, Iain; Brzezinska, Anna; Bucsics, Anna; Campbell, Stephen; Ferrario, Alessandra; Finlayson, Alexander; Furst, Jurij; et al. (Frontiers in Pharmacology, 2013)
Background: There are potential conflicts between authorities and companies to fund new premium priced drugs especially where there are safety and/ or budget concerns. Dabigatran, a new oral anticoagulant for the prevention of stroke in patients with non-valvular AF, exemplifies this issue. Whilst new effective treatments are needed, there are issues in the elderly with dabigatran due to variable drug concentrations, no known antidote and dependence on renal elimination. Published studies have shown dabigatran to be cost-effective but there are budget concerns given the prevalence of atrial fibrillation. There are also issues with potentially re-designing anticoagulant services. This has resulted in activities across countries to better manage its use. Objective: To (i) review authority activities in over 30 countries and regions, (ii) use the findings to develop new models to better manage the entry of new drugs , and (iii) review the implications for all major stakeholder groups. Methodology: Descriptive review and appraisal of activities regarding dabigatran and the development of guidance for groups through an iterative process. Results: There has been a plethora of activities to manage dabigatran including extensive pre-launch activities, risk sharing arrangements, prescribing restrictions and monitoring of prescribing post launch. Reimbursement has been denied in some countries due to concerns with its budget impact and/or excessive bleeding. Development of a new model and future guidance is proposed to better manage the entry of new drugs, centring on three pillars of pre-, peri- and post-launch activities. Conclusion: Models for introducing new drugs are essential to optimise their prescribing especially where there are concerns. Without such models, new drugs may be withdrawn prematurely and/ or struggle for funding.